1966
DOI: 10.1021/jf60148a027
|View full text |Cite
|
Sign up to set email alerts
|

Release of Volatile Selenium Compounds by Plants. Collection Procedures and Preliminary Observations

Abstract: was highest in sheaths and lowest in developing heads. Ash content of all plant parts except stems was higher in spring than in fall. Stems were only slightly lower in the spring. Percentage of silica in the ash was highest in the roots in spring, averaging 43.3%, and was lowest in developing heads (average of 9.80%).Spodograms representative of the silica deposition in various parts of the barley plants are shown in Figure 1. Considerable difference existed between the depositional pattern occurring in leaves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
52
0

Year Published

1983
1983
2014
2014

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(53 citation statements)
references
References 6 publications
1
52
0
Order By: Relevance
“…Selenium is unusual among trace elements because it can also be removed from the ground ecosystem by phytovolatilization, i.e. plants metabolize inorganic Se to relatively nontoxic, volatile forms (dimethyl selenide [DMSe] and dimethyl diselenide [DMDSe]), which escape to the atmosphere (Lewis et al, 1966;Terry et al, 2000). Selenium phytoremediation has been achieved under field conditions using fast-growing plant species, such as Indian mustard (Brassica juncea;Bañ uelos et al, 1997), which accumulates Se to hundreds of parts per million (Bañ uelos and Schrale, 1989).…”
mentioning
confidence: 99%
“…Selenium is unusual among trace elements because it can also be removed from the ground ecosystem by phytovolatilization, i.e. plants metabolize inorganic Se to relatively nontoxic, volatile forms (dimethyl selenide [DMSe] and dimethyl diselenide [DMDSe]), which escape to the atmosphere (Lewis et al, 1966;Terry et al, 2000). Selenium phytoremediation has been achieved under field conditions using fast-growing plant species, such as Indian mustard (Brassica juncea;Bañ uelos et al, 1997), which accumulates Se to hundreds of parts per million (Bañ uelos and Schrale, 1989).…”
mentioning
confidence: 99%
“…A large proportion of the Se removed by the wetland was accumulated in plant tissues and sediments, and it was estimated that 10% to 30% of the removed Se was volatilized. Se volatilization is the process by which inorganic Se is converted to volatile forms (Lewis et al, 1966;Evans et al, 1968;Lewis, 1971;Frankenberger and Karlson, 1994;Terry and Zayed, 1994). Dimethylselenide, the predominant form of volatile Se, is 500 to 700 times less toxic than inorganic forms of Se (McConnell and Portman, 1952;Ganther et al, 1966;Wilber, 1980).…”
mentioning
confidence: 99%
“…This process is called phytovolatilization, the most controversial of all phytoremediation technologies. According to Brooks (1998), the release of volatile Se compounds from higher plants was first reported by Lewis et al (1966). Terry et al (1992) reported that members of the Brassicaceae are capable of releasing up to 40 g Se ha -1 day -1 as various gaseous compounds.…”
Section: Phytovolatilizationmentioning
confidence: 99%